2014
DOI: 10.1007/s11248-014-9810-3
|View full text |Cite
|
Sign up to set email alerts
|

Establishment and optimization of a regionally applicable maize gene-flow model

Abstract: Because of the rapid development of transgenic maize, the potential effect of transgene flow on seed purity has become a major concern in public and scientific communities. Setting a proper isolation distance in field experiments and seed production is a possible solution to meet seed-quality standards and ensure adventitious contamination of products is below a specific threshold. By using a Gaussian plume model as basis and data recorded by meteorological stations as input, we have established a simple regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 33 publications
1
12
1
Order By: Relevance
“…Langhof et al (2010) found that an isolation distance of 50 m in the Germany is enough to make cross-pollination rate below 0.9% (Langhof et al, 2010). With a Gaussian plume model, Hu et al (2014) predicted that the maximum threshold distances were 10-49 m at which gene-flow frequency is lower than 1% using 101 meteorological data in the maize-growing region of Northeast China. Thus, isolation distance of 50 m is safe to meet the 0.9% threshold.…”
Section: Discussionmentioning
confidence: 99%
“…Langhof et al (2010) found that an isolation distance of 50 m in the Germany is enough to make cross-pollination rate below 0.9% (Langhof et al, 2010). With a Gaussian plume model, Hu et al (2014) predicted that the maximum threshold distances were 10-49 m at which gene-flow frequency is lower than 1% using 101 meteorological data in the maize-growing region of Northeast China. Thus, isolation distance of 50 m is safe to meet the 0.9% threshold.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, PMGF frequencies estimated from a limited number of field experiments may not represent PMGF frequencies of a particular plant species under diverse environmental conditions. As a comparison, mathematical modelling can provide relatively quick estimation of PMGF frequencies for different plant species under diverse environmental conditions (Yao et al 2008; Rong et al 2010; Hu et al 2014). Undoubtedly, mathematical modelling provides a powerful complement of the field-experiment-based method to estimate PMGF frequencies, provided that the model can accurately simulate PMGF (Rong et al 2010; Wang et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Many PMGF models have been established (Loos et al 2003; Klein et al 2006; Yao et al 2008; Wang and Yang 2010; Hu et al 2014). However, some of these models essentially simulate the variation patterns/dynamics of PMGF or describe parameters that affect PMGF frequencies (Loos et al 2003; Klein et al 2006).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations